Neuroendocrine tumor liver metastases : use of dynamic contrast-enhanced MR imaging to monitor and predict radiolabeled octreotide therapy response - Miyazaki, K. (2013)
Purpose: To evaluate dynamic contrast-enhanced (DCE) magnetic resonance (MR) imaging for monitoring and assessing treatment response in patients with neuroendocrine liver metastases treated using yttrium 90 (90Y)-labeled octreotide (90Y-DOTATOC).